A baker’s dozen of issues facing online academic journal start-ups - Gould, Thomas H. P. (My University, 2013)
The rapid upsurge in online academic journal creation, publishing, and management has challenged researchers and universities. Much of the recent flurry of activity has happened while guidelines and protocol are being created. This article outlines the nature of the increased publication of these new journals, as well as offers advice in 13 areas that journal editors and boards will face. This article is based on the findings of academics in a wide variety of academic fields, including library science, as well as the author’s own experience as an online journal editor.
Keywords: Online academic research journals; Online publishing; Born-digital